1996
DOI: 10.1111/j.1467-8683.1996.tb00136.x
|View full text |Cite
|
Sign up to set email alerts
|

The Case for Separating the Roles of Chairman and CEO: An Analysis of Stock Market and Accounting Data

Abstract: This UK study investigates whether the stock market prefers companies to award the positions of chairman and chief executive officer to two different people instead of permitting a single individual, the 'dual CEO', to combine them. The results suggest (a) that the market responds favourably to the separation of the two roles and unfavourably to their fusion and (b) that the accounting performance of companies which adopt a 'dual CEO' appears to decline subsequent to this change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
104
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(117 citation statements)
references
References 18 publications
12
104
0
1
Order By: Relevance
“…We find a significant positive link between DBLS and market valuation, but only in firms with independent chairpersons, implying that the market values firms with independent DBLS more highly. Our evidence provides support for both the recommendations of King II and the findings of previous studies (Rechner and Dalton, 1991;Dahya et al, 1996) that report a positive association between DBLS and market valuation, but inconsistent with those that either report a negative (Boyd, 1995;Kiel and Nicholson, 2003) or no (Baliga et al, 1996;Bozec, 2005) association. The findings are robust across a number of econometric models that control for different types of market valuation proxies and endogeneity problems.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…We find a significant positive link between DBLS and market valuation, but only in firms with independent chairpersons, implying that the market values firms with independent DBLS more highly. Our evidence provides support for both the recommendations of King II and the findings of previous studies (Rechner and Dalton, 1991;Dahya et al, 1996) that report a positive association between DBLS and market valuation, but inconsistent with those that either report a negative (Boyd, 1995;Kiel and Nicholson, 2003) or no (Baliga et al, 1996;Bozec, 2005) association. The findings are robust across a number of econometric models that control for different types of market valuation proxies and endogeneity problems.…”
Section: Discussionsupporting
confidence: 68%
“…Our evidence also provides support for both the recommendations of King II and the findings of previous studies (Rechner and Dalton, 1991;Dahya et al, 1996) that report a positive association between DBLS and market valuation, but inconsistent with those that either report a negative (Boyd, 1995;Kiel and Nicholson, 2003) or no (Baliga et al, 1996;Bozec, 2005) association. …”
Section: Cg Ntim Does the South African Stock Market…supporting
confidence: 70%
See 1 more Smart Citation
“…Bliss (2011) stated that CEO duality is an obstacle for the independence of the board. Researchers such as Brickley et al (1997); Dahya et al (1996) argued that a dual CEO role was important as it reduced chances of clashes on viewpoint and enabled timely decision making. Several other studies (De Oliveira Gondrige et al, 2012;Dharmadasa et al, 2014;Schmid & Zimmermann, 2008) found no correlation between dual CEO role and performance of firm.…”
Section: Duality and Firm Performancementioning
confidence: 99%
“…Previous studies like Dahya, Lonie, andPower (1996), Carter, Simkins, andSimpson (2003), Branco and Rodrigues (2008), and Khan (2010) showed the positive relation between CSR reporting and corporate governance. According to Fama and Jensen (1983), increasing number of non-executive members on the board is a useful tool to solve the conflicts between managers and owners.…”
Section: Research Purpose and Hypothesesmentioning
confidence: 99%